Introduction to microbiota: agents for health and disease - Finlay, B. Brett (Henry Stewart Talks, 2011)
Microbiota, an overview, What the microbiota is comprised of, Benefits of the microbiota, Diseases associated with changes in microbiota, Obesity, Allergic diseases, Bowel diseases
Reviewed at 2015/10/26